2019
DOI: 10.1002/adom.201801667
|View full text |Cite
|
Sign up to set email alerts
|

An Organic Emitter Displaying Dual Emissions and Efficient Delayed Fluorescence White OLEDs

Abstract: number of one-compound-based efficient white light photoluminescence (PL) have been reported. [3] The performance of the single-emitter-based WOLEDs should be improved. [4] As a consequence, highly efficient organic white electroluminescence (EL) based on one emissive compound is still a great challenge. A fundamental issue is to construct organic molecules that can form two kinds of electron-injection-induced excited states with blue and yellow emission characteristics. Furthermore, elucidating and understa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 44 publications
1
24
1
Order By: Relevance
“…The combination of blue and yellow emissions from a semi-crystalline film of 24 resulted in WOLEDs with a maximum EQE of 6.2% and CIE (0.34, 0.46). 11 The existence of two ground-state conformers, with different singlet-triplet energy gaps (1.14 and 0.18 eV) arising from the distortion of the phenothiazine unit, was confirmed by both theoretical and experimental results for the triazine derivative 25. Interestingly, both ax and eq excited state conformers of the PTZ unit exhibited CT emission.…”
Section: Dual Prompt and Delayed Photoluminescencementioning
confidence: 80%
See 2 more Smart Citations
“…The combination of blue and yellow emissions from a semi-crystalline film of 24 resulted in WOLEDs with a maximum EQE of 6.2% and CIE (0.34, 0.46). 11 The existence of two ground-state conformers, with different singlet-triplet energy gaps (1.14 and 0.18 eV) arising from the distortion of the phenothiazine unit, was confirmed by both theoretical and experimental results for the triazine derivative 25. Interestingly, both ax and eq excited state conformers of the PTZ unit exhibited CT emission.…”
Section: Dual Prompt and Delayed Photoluminescencementioning
confidence: 80%
“…10 In contrast to systems composed of several fluorescent molecules, single-molecular systems with white emission through DE have several advantages: they can avoid the drawbacks of phase separation, colour aging, and degradation; moreover, they lead to enhanced reproducibility and stability, as well as simpler device fabrication. 11,12 However, the design of purely organic molecules capable of blue/yellow DE suitable for efficient WOLEDs requires in-depth understanding of the different DE mechanisms. As an additional complication, 11 ideal WOLEDs should also harvest the electro-generated excited triplet states in order to reach the highest internal quantum efficiency of 100% by utilizing thermally activated delayed fluorescence (TADF) 13 or phosphorescence (PH) 14 most commonly for the yellow-emitting excited state.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…29) consisting of a PTZ donor and a BP acceptor. 100 The PL spectra of PTZ-BP in diluted toluene solution at room temperature and low temperature showed two maximum emission values at 440 nm and 550 nm, respectively, and the emission at 550 nm showed typical TADF characteristics. The X-ray structure of the single crystal and PL spectra showed that the two emission peaks were derived from the H-extra and H-intra conformations of PTZ-BP, respectively.…”
Section: Ptz Based Emittersmentioning
confidence: 89%
“…To achieve dual emission, a series of strategies have been reported, such as by forming excimers ( Lee et al, 2014 ; Chen et al, 2016 ), combining intra- and intermolecular charge transfer ( Li et al, 2019 ; Wen et al, 2020 ), and constructing supramolecular self-assembles ( Pal et al, 2017 ; Li et al, 2018 ; Wang et al, 2020 ) and excited-state intramolecular proton transfer (ESIPT) emission ( Sakai et al, 2016 ; He et al, 2018 ; Li et al, 2018 ; Sedgwick et al, 2018 ; Suzuki et al, 2018 ; Wu et al, 2018 ). As a good approach that can rationally tune the dual-emission property, ESIPT involves a rapid photoinduced tautomerization of a molecule in its electronic excited state, in which the protons are prone to transfer to adjacent heteroatoms through intramolecular hydrogen bonding forming excited-state isomers, i.e., from the enol (E*) to keto (K*) formula ( Figure 1A ).…”
Section: Introductionmentioning
confidence: 99%